PSYCHOLOGICAL INDICATORS OF THE WORK OF THE MANAGER WITH THE PERSONAL STRUCTURE OF THE NATIONAL POLICE OF UKRAINE - Barko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article is devoted to the problem of training the heads of units of the National Police to implement effective personnel management. The activities of the police are among the complex, it is accompanied by significant physical and psychological stress on police officers, often containing threats to their lives and health. The article focuses on the idea of a proactive approach that underlies the modern concepts of police management and is designed to provide psychological prevention of problems in the police organization, prevention of conflicts, stress, police discontent. The article reveals the psychological conditions for the manager to carry out such proactive management, emphasizes the need for special psychological training of police managers through vocational psychological training.